Added value of three‐dimensional transesophageal echocardiography in management of mitral paravalvular leaks - Mahmoud‐Elsayed, Hani (Echocardiography (Mount Kisco, N.Y.), 2020)
Prosthetic paravalvular leak (PVL) is a well‐known serious complication following surgically as well as percutaneously implanted prosthetic valves. It usually happens due to incomplete sealing of the prosthetic ring to the native cardiac tissue whether immediately postoperative or considerably later as a complication of infective endocarditis, etc Surgery has been always the treatment of choice for clinically significant PVLs. However, percutaneous transcatheter closure therapy has become a successful alternative in carefully selected group of patients. Echocardiography is a cornerstone in the initial diagnosis, assessment of the severity and location of the PVL. Furthermore, it plays a crucial role in the assessment of the feasibility for percutaneous closure and during intra‐procedural guidance. Transesophageal echocardiography (TEE) has the advantage over transthoracic echocardiography (TTE) of not being affected by the acoustic shadow of the mitral prosthesis that usually hides the regurgitation jets and makes TTE evaluation difficult. Three‐dimensional (3D) TEE has been shown to provide better diagnostic accuracy compared to two‐dimensional (2D) TEE as regard to evaluation of PVLs especially in patients with more than one PVL. This is due to better delineation of the location, shape, and size of the PVL and equally important during guiding the transcatheter percutaneous closure.